A systems modelling approach to predict biological responses to extreme heat - Daniel W.A. Noble; Margaret M. Mayfield; Ary A. Hoffmann; Zhong-Hua Chen; Steven J. Lade; Xuemei Bai; Danielle A. Way; Belinda E. Medlyn; Owen K. Atkin; Adrienne B. Nicotra; James M. Cook; Brajesh K. Singh; et al. (Trends in Ecology & Evolution, 2026)

Mind the gap: global targets and strategies for ex situ conservation of critically endangered plants - Kiran L. Dhanjal-Adams; Itxaso Quintana; Daniel Ballesteros; Naomi Carvey; Udayangani Liu; Michael Way; Juan Viruel; Elinor Breman (Biodiversity and Conservation, 2026)
An estimated 45% of plants are threatened with extinction, with those classified as “Critically Endangered” (CR) by the International Union for Conservation of Nature at the highest risk and in urgent need of ex situ conservation. We performed a gap analysis of CR plants stored in in the Millennium Seed Bank Partnership (MSBP), a global network spanning 101 countries and territories, to assess their current conservation status and guide future seed collection priorities. The MSBP currently holds 2,507 accessions of 474 CR taxa, representing 0.9% of the 52,874 taxa banked and 7.21% of all CR taxa. While most collections have relatively good general information available (information index = 0.81), key aspects such as viability (viability index = 0.31) and genetic diversity (genetic diversity index = 0.31) remain poorly documented. Only 9.49% of conserved CR taxa have sufficient seed numbers (≥ 1,050 seeds from ≥ 50 individuals) for restoration research, and just 5.49% have been collected from ≥ 5 populations and ≥ 50 individuals across their native distribution. Overall, 6,120 CR plant taxa remain unbanked, of which 11.58 to 17.17% (depending on model) require alternative conservation methods due to desiccation-intolerant seeds. However, the majority (23.32–68.74% taxa) are likely suitable for traditional seed banking techniques (drying to 15% relative humidity and freezing at -20℃). The desiccation sensitivity of 14.02–65.16% taxa remains unknown, requiring urgent research. Ensuring comprehensive ex situ conservation of CR taxa will require strategic investment and capacity building to meet global biodiversity conservation needs.

Prioritisation of native trees for enhancing carbon sequestration in shade-grown coffee plantations in the State of Veracruz (México): linking conservation and ecological traits to community needs - Cesar Mateo Flores-Ortiz; Patricia Davila; Isela Rodríguez-Arevalo; Robert Hunter Manson; María Toledo-Garibaldi; Daniel Cabrera-Santos; María Alejandra Salguero; Flor Gabriela Vázquez; Jazmin Cobos-Silva; Maraeva Gianella; Elizabeth Bell; Michael Way; et al. (Agroforestry Systems, 2025)
Agroforestry systems, such as shade-grown coffee plantations are particularly well suited to address the challenges of climate change, due to potential synergies between adaptation and mitigation strategies. The traditional knowledge of coffee producers can play a critical role in optimizing agroforestry approaches and shade tree selection to balance biodiversity conservation and local needs. This knowledge was used in a two-stage hybrid methodology identifying the shade tree species that help coffee growers in central Veracruz, México, face multiple challenges including climate change, biodiversity conservation, and improved livelihoods. Multi-criteria decision analysis using the distribution and conservation traits and agroecological information available of the native tree species of Veracruz, helped generate a preliminary list of 50 prioritised species, which was refined by incorporating local knowledge of each species in participatory workshops involving smallholder producers, where gender equality and social inclusion principles were applied. Species with the highest priority score were those belonging to the genus Inga ( I. jinicuil, I. vera, I. punctata ), which provides shade, soil fertility, bird habitat, and food. Domesticated species of the genera Persea ( P. americana, P. schiedeana, P. longipes ) and Psidium ( P. guajava ), were also prioritised as they are considered as important elements for shade and fruit production. This methodology combines distribution and conservation and ecological traits with local knowledge to prioritise native tree species for use in shade-grown coffee plantations in the central region of Veracruz. This multidisciplinary approach could be replicated more broadly in México and other coffee growing regions.

Translational Molecular Imaging Tool of Vulnerable Carotid Plaque: Evaluate Effects of Statin Therapy on Plaque Inflammation and American Heart Association–Defined Risk Levels in Cuff-Implanted Apolipoprotein E–Deficient Mice - Joyce M. S. Chan; Sung-Jin Park; Michael Ng; Way Cherng Chen; Wan Ying Chan; Kishore Bhakoo; Tze Tec Chong (Translational Stroke Research, 2024)
Identification of high-risk carotid plaques in asymptomatic patients remains a challenging but crucial step in stroke prevention. The challenge is to accurately monitor the development of high-risk carotid plaques and promptly identify patients, who are unresponsive to best medical therapy, and hence targeted for carotid surgical interventions to prevent stroke. Inflammation is a key operator in destabilisation of plaques prior to clinical sequelae. Currently, there is a lack of imaging tool in routine clinical practice, which allows assessment of inflammatory activity within the atherosclerotic plaque. Herein, we have used a periarterial cuff to generate a progressive carotid atherosclerosis model in apolipoprotein E–deficient mice. This model produced clinically relevant plaques with different levels of risk, fulfilling American Heart Association (AHA) classification, at specific timepoints and locations, along the same carotid artery. Exploiting this platform, we have developed smart molecular magnetic resonance imaging (MRI) probes consisting of dual-targeted microparticles of iron oxide (DT-MPIO) against VCAM-1 and P-selectin, to evaluate the anti-inflammatory effect of statin therapy on progressive carotid atherosclerosis. We demonstrated that in vivo DT-MPIO-enhanced MRI can (i) quantitatively track plaque inflammation from early to advanced stage; (ii) identify and characterise high-risk inflamed, vulnerable plaques; and (iii) monitor the response to statin therapy longitudinally. Moreover, this molecular imaging–defined therapeutic response was validated using AHA classification of human plaques, a clinically relevant parameter, approximating the clinical translation of this tool. Further development and translation of this molecular imaging tool into the clinical arena may potentially facilitate more accurate risk stratification, permitting timely identification of the high-risk patients for prophylactic carotid intervention, affording early opportunities for stroke prevention in the future.

Conserving useful plants for a sustainable future: species coverage, spatial distribution, and conservation status within the Millennium Seed Bank collection - Udayangani Liu; Maraeva Gianella; Patricia Dávila Aranda; Mauricio Diazgranados; César Mateo Flores Ortíz; Rafael Lira-Saade; Silvia Bacci; Efisio Mattana; William Milliken; Olivia Mitrovits; Hugh W. Pritchard; Isela Rodríguez-Arévalo; et al. (Biodiversity and Conservation, 2023)
A substantially rich diversity of the world’s recorded useful plants (UPs) is captured within the Millennium Seed Bank collection hosted by the Royal Botanic Gardens, Kew, at Wakehurst, UK with 13,598 species (34%) belonging to 3696 genera and 325 families. This constitutes just over half of the total accessions and one third of the species and covers all 9 continents, 8 realms, 14 biomes, 34 biodiversity hotspots and 175 countries. The most common beneficial use category within the captured diversity is medicinal, then species with environmental, material, and human food value. About 86% of conserved UP species have a ‘Least Concern’ conservation status but 8% are identified as globally threatened. The advantages of mutual, continued, and long-term partnership (e.g., Mexico) are showcased when conserving plants important for local communities and addressing conservation challenges beyond seed banking. However, the geographic coverage suffers from a lack of partnerships with some parts of the world. Also, a low number of accessions contributed from many countries means that insufficient native range is yet to be captured for many species. This is particularly the case for restricted or narrow distribution species from families or genera with a high incidence of recalcitrant or short-lived seeds. Future planning must tailor better to cover the spatial distribution patterns for individual species, thereby improving the number of accessions and geographical coverage for those captured. Moreover, seed biology research should characterise desiccation tolerance and develop complementary, novel conservation methods, such as cryopreservation, to strengthen conservation options for UP species.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

The insect-killing bacterium Photorhabdus luminescens has the lowest mutation rate among bacteria - Jiao Pan; Emily Williams; Way Sung; Michael Lynch; Hongan Long (Marine Life Science & Technology, 2021)
Mutation is a primary source of genetic variation that is used to power evolution. Many studies, however, have shown that most mutations are deleterious and, as a result, extremely low mutation rates might be beneficial for survival. Using a mutation accumulation experiment, an unbiased method for mutation study, we found an extremely low base-substitution mutation rate of 5.94 × 10 –11 per nucleotide site per cell division (95% Poisson confidence intervals: 4.65 × 10 –11 , 7.48 × 10 –11 ) and indel mutation rate of 8.25 × 10 –12 per site per cell division (95% confidence intervals: 3.96 × 10 –12 , 1.52 × 10 –11 ) in the bacterium Photorhabdus luminescens ATCC29999. The mutations are strongly A/T-biased with a mutation bias of 10.28 in the A/T direction. It has been hypothesized that the ability for selection to lower mutation rates is inversely proportional to the effective population size (drift-barrier hypothesis) and we found that the effective population size of this bacterium is significantly greater than most other bacteria. This finding further decreases the lower-bounds of bacterial mutation rates and provides evidence that extreme levels of replication fidelity can evolve within organisms that maintain large effective population sizes.

Assessing seed desiccation responses of native trees in the Caribbean - Efisio Mattana; Brígido Peguero; Alice Di Sacco; Wilvin Agramonte; Wilkin Rafael Encarnación Castillo; Francisco Jiménez; Teodoro Clase; Hugh W. Pritchard; Pablo Gómez-Barreiro; Elena Castillo-Lorenzo; Marianny Terrero Encarnación; Michael J. Way; et al. (New Forests, 2020)
Native trees from the Caribbean were tested for seed desiccation responses, by adapting the “100-seed test” protocol. Ninety-seven seed lots of 91 species were collected in the Dominican Republic and tested for germination immediately after collecting, and after drying and moist storage. Seed desiccation sensitivity was assessed as a continuous variable (Viability Loss Index; VLI), based on seed germination values before and after drying. The results were compared with predictions of seed desiccation responses based on seed lot traits (initial moisture content and thousand-seed weight) and with those of published predictive models based on plant and seed traits. VLI could be calculated for seed lots of 40 species. 80% of these seed lots showed consistent results among experiments and predictive models. Issues on the set up of the experiments were discussed, as well as the species for which experimental results and predictions led to contrasting results. Overall, the “100-seed test” confirmed to be an effective tool for assessing seed desiccation responses of a diverse under-investigated woody flora, guiding the seed conservation of trees and their use in reforestation programmes. In addition, by providing new data, it might improve the performance of available predictive models.

Taxon‐ and vector‐specific variation in species richness and abundance during the transport stage of biological invasions - Elizabeta Briski; Sarah A. Bailey; Oscar Casas-Monroy; Claudio DiBacco; Irena Kaczmarska; Janice E. Lawrence; Jonas Leichsenring; Colin Levings; Michael L. MacGillivary; Christopher W. McKindsey; Leslie E. Nasmith; Marie Parenteau; et al. (Limnology and Oceanography, 2013)
Recent empirical and statistical evidence suggest that propagule pressure (i.e., number of individuals introduced per event, and the number and frequency of events) and colonization pressure (i.e., number of species released per event, and the number and frequency of events) are of vital importance to invasion success. To explore possible changes in propagule and colonization pressure during the transport stage of the invasion process, we examine abundance and species richness of virus‐like particles, bacteria, diatoms, dinoflagellates, and invertebrates transported in commercial ships—a leading vector for global spread of aquatic nonindigenous species. We collected 154 ballast water samples from ships that had performed or were exempt from ballast water exchange (BWE) prior to arrival at Pacific and Atlantic ports in Canada and Laurentian Great Lakes ports. We found that abundance and species richness varied across taxa and regions, with ships arriving to the Atlantic region carrying the highest abundance of taxa. The highest species richness of invertebrates and diatoms was recorded from ships arriving to the Pacific, whereas the richest communities of dinoflagellates occurred in the Atlantic region. We also found that BWE had no effect on abundance or species richness of most taxa (dinoflagellates, diatoms, bacteria, and virus‐like particles), whereas the effect on abundance of invertebrates was not clear. Finally, longer voyages resulted in lower abundance of all taxa except dinoflagellates, and lower species richness of diatoms. Paradoxically, the elevated abundance and species richness of dinoflagellates following BWE suggest that this group could have enhanced invasion potential when ships manage ballast water by exchange.

The Role of Botanic Gardens in the Science and Practice of Ecological Restoration - KATE A. HARDWICK; PEGGY FIEDLER; LYNDON C. LEE; BRUCE PAVLIK; RICHARD J. HOBBS; JAMES ARONSON; MARTIN BIDARTONDO; ERIC BLACK; DAVID COATES; MATTHEW I. DAWS; KINGSLEY DIXON; STEPHEN ELLIOTT; et al. (Conservation Biology, 2011)
Many of the skills and resources associated with botanic gardens and arboreta, including plant taxonomy, horticulture, and seed bank management, are fundamental to ecological restoration efforts, yet few of the world's botanic gardens are involved in the science or practice of restoration. Thus, we examined the potential role of botanic gardens in these emerging fields. We believe a reorientation of certain existing institutional strengths, such as plant‐based research and knowledge transfer, would enable many more botanic gardens worldwide to provide effective science‐based support to restoration efforts. We recommend botanic gardens widen research to include ecosystems as well as species, increase involvement in practical restoration projects and training practitioners, and serve as information hubs for data archiving and exchange.

Enhanced single copy integration events in corn via particle bombardment using low quantities of DNA - Brenda A. Lowe; N. Shiva Prakash; Melissa Way; Michael T. Mann; T. Michael Spencer; Raghava S. Boddupalli (Transgenic Research, 2009)